Peran Malassezia spp. pada Dermatitis Seboroik: Literature Review - Vinolia Sandhyano Alkautsar Putri Walyatalattof; Hapsari Triandriyani; Hadi Firmansyah S. (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Seborrheic dermatitis (SD) is a chronic, recurrent inflammatory skin disorder that commonly affects sebaceous-rich areas such as the scalp and central face. Although multifactorial, Malassezia spp., particularly M. globosa and M. restricta, play a central etiologic role. These lipophilic yeasts, part of the normal skin microbiota, can become opportunistic pathogens under conditions of dysbiosis, excessive sebum production, or barrier dysfunction. Metabolic products such as oleic acid disrupt epidermal integrity and induce keratinocyte hyperproliferation, while activation of pattern recognition receptors (PRRs) triggers IL-23/IL-17–mediated immune responses. This review aims to elucidate the pathogenic role of Malassezia spp. in SD and its clinical implications. Understanding this host–microbe interaction allows for targeted therapy emphasizing antifungal and anti-inflammatory strategies. By elucidating these mechanisms, new therapeutic approaches, such as antifungal agents and anti-inflammatory treatments, can be designed to better manage SD and improve patient outcomes. Understanding the role of Malassezia in SD highlights the importance of a balanced skin microbiome in maintaining skin health and preventing chronic inflammatory skin disorders.